2020
DOI: 10.1186/s42836-020-00052-6
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of femoral component rotational measurements using computed tomography—a cadaveric study

Abstract: Background CT scans can be used to assess the rotational alignment of the femoral component following total knee arthroplasty (TKA). This is done by calculating the posterior condylar angle (PCA). However, the methods used may not account for the biomechanical functionality of the TKA components. This cadaveric study aimed to determine whether the axis of scanning (mechanical or anatomical) alters the results of PCA calculations. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Some in vitro and in vivo studies have shown that the posterior condyles appear circular and the centers pass through the medial and lateral femoral epicondyles, which coincides with the epicondylar axis 1,9 . Therefore, the epicondylar axis has been proposed as a reliable reference for determining the rotational alignment of the femoral component in total knee arthroplasty 21 . However, some studies have come to a different conclusion, that the epicondylar axis does not coincide with the contour of the femoral condyles 12,13,27 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some in vitro and in vivo studies have shown that the posterior condyles appear circular and the centers pass through the medial and lateral femoral epicondyles, which coincides with the epicondylar axis 1,9 . Therefore, the epicondylar axis has been proposed as a reliable reference for determining the rotational alignment of the femoral component in total knee arthroplasty 21 . However, some studies have come to a different conclusion, that the epicondylar axis does not coincide with the contour of the femoral condyles 12,13,27 .…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 9 Therefore, the epicondylar axis has been proposed as a reliable reference for determining the rotational alignment of the femoral component in total knee arthroplasty. 21 However, some studies have come to a different conclusion, that the epicondylar axis does not coincide with the contour of the femoral condyles. 12 , 13 , 27 Lustig et al investigated the existence of a circle centering on the epicondyles and fitting the whole femoral contours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations